Unquestioned Traditions and Social Compliance in The Lottery: A Sociological Perspective - Zahyra Putri Aulia; Devy Camelia; Viva Stevany Netanya Br Tarigan; Adib Zahirrifa; Shafira Al Ikhwani; T. Thyrhaya Zein (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2026)
This study aims to analyze the representation of tradition, social compliance, and collective violence in The Lottery by Shirley Jackson using a sociological approach to literature. This research employs a qualitative method through textual analysis, where data in the form ofwords, phrases, and sentences related to the research themes are identified and analyzed thematically. The primary theoretical framework used is sociology of literature to examine social structures within the text, while social conformity theory serves as a supportingframework to explain individual behavior within a group. The findings reveal that tradition in the story functions as a social structure that persists despite the loss of its original meaning. This tradition is internalized by the community, resulting in strong social compliance in which individuals follow norms without questioning their moral implications. Such compliance contributes to the normalization of violence, which is collectively carried out by the community. Therefore, violence in the narrative is not an individual act but a product of anestablished social system. In conclusion, the study highlights that the interaction between tradition and social conformity can lead to the acceptance of harmful practices within society. Thus, critical awareness is necessary to evaluate existing norms and prevent the continuation of unjust social practices.Keywords: Collective violence, social compliance, sociology of literature, tradition.